Molecular mechanisms of Cr(VI) resistance in bacteria and fungi. Issue 4 (3rd December 2013) - Viti, Carlo; Marchi, Emmanuela; Decorosi, Francesca; Giovannetti, Luciana
Abstract Hexavalent chromium [Cr(VI)] contamination is one of the main problems of environmental protection because the Cr(VI) is a hazard to human health. The Cr(VI) form is highly toxic, mutagenic, and carcinogenic, and it spreads widely beyond the site of initial contamination because of its mobility. Cr(VI), crossing the cellular membrane via the sulfate uptake pathway, generates active intermediates Cr(V) and/or Cr(IV), free radicals, and Cr(III) as the final product. Cr(III) affects DNA replication, causes mutagenesis, and alters the structure and activity of enzymes, reacting with their carboxyl and thiol groups. To persist in Cr(VI)‐contaminated environments, microorganisms must have efficient systems to neutralize the negative effects of this form of chromium. The systems involve detoxification or repair strategies such as Cr(VI) efflux pumps, Cr(VI) reduction to Cr(III), and activation of enzymes involved in the ROS detoxifying processes, repair of DNA lesions, sulfur metabolism, and iron homeostasis. This review provides an overview of the processes involved in bacterial and fungal Cr(VI) resistance that have been identified through 'omics' studies. A comparative analysis of the described molecular mechanisms is offered and compared with the cellular evidences obtained using classical microbiological approaches.